If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 2m + -18 Reorder the terms: 0 = -18 + 2m Solving 0 = -18 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 0 + -2m = -18 + 2m + -2m Remove the zero: -2m = -18 + 2m + -2m Combine like terms: 2m + -2m = 0 -2m = -18 + 0 -2m = -18 Divide each side by '-2'. m = 9 Simplifying m = 9
| -0.3f+1.3=4.8 | | -18/y+3 | | (x+16)+(x+22)=231 | | y^2-3y/y+3 | | 5(4x)-1/2x=234 | | 9h+4.5-7h+1.75= | | 6x+3x-3= | | 12+7C=103 | | 21-1y=-87+2y | | 6y-5-2y=-31 | | -2/3n-6=18 | | -7+28m=13(2m-3) | | 2v-54=-1v+21 | | 0.5n+0.3n-0.4n= | | 2x=14+2 | | 12-7y=40 | | 12x+y-x+6y= | | 7x-2x+2-x= | | 6n+10=-44 | | 2/3k=4/3 | | 4x^2+176=0 | | 8p-9=49 | | 2x^2+19+24=0 | | 2x/7-2x=x/2+17/2 | | 12/3+4-24/3x8 | | 5+(2-x)/3=7 | | K/4+5=4 | | 4x-9x=45 | | 2.5y-0.25y= | | -4=-1+c/5 | | 8m^2-2m=11 | | 4(2b+6)+11=-8b-13 |